Cytaty i plagiaty. Tekst piosenki i wypowiedzi slamerskie w świetle prawa autorskiego - Świerkowska, Dagmara (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2021)
The most important function of copyright is the protection of products of creativity, property rights and personal creator. In this broad sense, the laws protecting the author are understood and accepted by practice all over the world. The main focus of this article is to analyse the lyrics of Polish songs whose authors entered the judicial path to investigate one’s rights, and to compare them with spoken word texts, which, due to frequent references to the works of other authors, could be considered illegal. The research material consists of open court judgments, song lyrics and recordings of slam poetry texts collected by the author.